2006
DOI: 10.2134/jeq2005.0099
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Load ofCryptosporidium parvumOocysts from Cattle Manure in Feedlots from the Central and Western United States

Abstract: The first step in assessing the risk of water contamination by Cryptosporidium parvum oocysts from feedlot cattle (Bos taurus) production systems is to quantify the number of C. parvum oocysts present in the fecal material deposited by feedlot cattle. Our primary objective for this project was to estimate the daily environmental load of C. parvum oocysts in fecal material deposited by feedlot cattle from across the central and western USA. Our secondary goal was to genotype isolates of C. parvum from feedlot c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
30
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 43 publications
0
30
0
Order By: Relevance
“…Phylogenetic analyses were conducted in MEGA4 (Tamura et al 2007) oocysts in their feces. A prevalence of around 1% has also been reported in feedlot cattle in North America (Atwill et al 2006). In Japan, Saeki et al (2000) could only detect C. parvum in one (0.2%) out of 582 adult cattle in Hyogo prefecture.…”
Section: Discussionmentioning
confidence: 96%
“…Phylogenetic analyses were conducted in MEGA4 (Tamura et al 2007) oocysts in their feces. A prevalence of around 1% has also been reported in feedlot cattle in North America (Atwill et al 2006). In Japan, Saeki et al (2000) could only detect C. parvum in one (0.2%) out of 582 adult cattle in Hyogo prefecture.…”
Section: Discussionmentioning
confidence: 96%
“…Cryptosporidium oocysts are a threat to water supplies because they are resistant to chlorine disinfection, have a low infectious dose, and are excreted by almost all vertebrates (6). Although farm animals and humans have generally been considered major sources of human-pathogenic Cryptosporidium oocysts in surface water (1,12,13,17,26), wildlife has been shown to play a significant role in the overall contamination of water with Cryptosporidium spp. through aquatic activities and runoff (5,8,9,11,15,16,19,20).…”
mentioning
confidence: 99%
“…The very low level of infection of mature cows with C. parvum suggests that field practices be developed and used to manage manure and potential runoff for young cattle likely to shed this pathogen. In the western United States, a study involving more than 5200 fecal samples, from 22 sites in seven states, showed that fresh fecal material from feedlot systems contained about 1.3 to 3.6 C. parvum oocysts/g feces, or about 2.8 × 10 4 to 1.4 × 10 5 oocysts/ animal-day (Atwill et al, 2006).…”
Section: Protozoan and Helminthic Parasitesmentioning
confidence: 99%
“…The very low level of infection of mature cows with C. parvum suggests that field practices be developed and used to manage manure and potential runoff for young cattle likely to shed this pathogen. In the western United States, a study involving more than 5200 fecal samples, from 22 sites in seven states, showed that fresh fecal material from feedlot systems contained about 1.3 to 3.6 C. parvum oocysts/g feces, or about 2.8 × 10 4 to 1.4 × 10 5 oocysts/ animal-day (Atwill et al, 2006).Clearly, data are needed to evaluate the effectiveness of various field management practices designed to reduce pathogen loading and transport off-site within largescale animal production areas. Runoff from cattle grazing areas as well as feeding and holding/resting lots may have off-site impacts if appropriate catchment and diversion measures are not available or are incorrectly implemented.…”
mentioning
confidence: 99%